Comparison of the tolerability and efficacy of intra-rectal lidocaine gel with peri-prostatic nerve block as anaesthetic techniques for prostate biopsy - Musliu Adetola Tolani; Muhammed Ahmed; Ahmad Tijjani Lawal; Lovely Fidelis; Abdullahi Sudi; Babatunde Kolapo Hamza; Mudi Awaisu; Oyelowo Nasir; Ahmad Bello; Hussaini Yusuf Maitama (African Journal of Urology, 2020)
Abstract Background Prostate biopsy is a painful procedure. However, over the years, varied opinions exist among urologists about the methods of achieving optimal pain relief for the procedure. The purpose of this study was to compare the tolerability of administration and the efficacy of intra-rectal lidocaine gel with peri-prostatic nerve block for this procedure. Methods From June 2016 to June 2017, 110 patients who met the study criteria were randomized to receive either intra-rectal lidocaine gel (Group 1) or an apical peri-prostatic nerve block (Group 2) for prostate biopsy. Their level of pain perception during the anaesthesia administration and the prostate biopsy was assessed using the Numeric Rating Scale. Other biopsy-related complications and patient satisfaction were also evaluated. Grouped data were compared using student t test and Chi-square with p < 0.05 considered significant. Results The pain score during the administration of anaesthesia was 1.6 ± 1.9 and 3.7 ± 2.1 for the intra-rectal lidocaine gel and peri-prostatic nerve block groups, respectively (p = 0.001). However, during the prostate biopsy, the pain score was 6.8 ± 2.2 and 2.9 ± 1.9 for the intra-rectal lidocaine gel and peri-prostatic nerve block groups, respectively (p = 0.001). There was a significantly lower rate of satisfaction (45.3% versus 86.8%, p = 0.001) in the lidocaine gel group. Conclusions Although intra-rectal lidocaine gel administration is better tolerated by patients, a peri-prostatic nerve block is more effective and provides better patient satisfaction than intra-rectal lidocaine gel when used as anaesthesia for prostate biopsy.